Kinetics of Methylene Blue Reduction with Oxalic Acid by Visible Spectrophotometric Method - AZMAT, RAFIA; YASMEEN, BINA; UDDIN, FAHIM (Asian Journal of Chemistry, 2010)
The redox reaction between methylene blue (MB) and oxalic acid was followed qualitative interpretation and spectrophotometrically for quantitive determination. This investigation compares spectrophotometric studies of MB+ reduction by oxalic acid at acidic pH. The colour loss of MB+ was observed at 668 nm showed that the reaction follows identical kinetics with respect to dye, reductant and HCl. The slow reaction with oxalic acid was observed in absence of acid. Regeneration of MB+ colour by reaction with dissolved oxygen of atmosphere was observed. The effect of change in ionic strength shows no significant change to extent of reaction. Reaction effected by change in temperature and activation parameters were computed. A mechanism consistent based on above conclusion has also been proposed.